Generation and Characterization of Erythroid Cells from Human Embryonic Stem Cells and Induced Pluripotent Stem Cells: An Overview. (26th October 2011) - Chang, Kai-Hsin; Bonig, Halvard; Papayannopoulou, Thalia
Abstract : Because of the imbalance in the supply and demand of red blood cells (RBCs), especially for alloimmunized patients or patients with rare blood phenotypes, extensive research has been done to generate therapeutic quantities of mature RBCs from hematopoietic stem cells of various sources, such as bone marrow, peripheral blood, and cord blood. Since human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) can be maintained indefinitely in vitro, they represent potentially inexhaustible sources of donor-free RBCs. In contrast to other ex vivo stem-cell-derived cellular therapeutics, tumorigenesis is not a concern, as RBCs can be irradiated without marked adverse effects on in vivo function. Here, we provide a comprehensive review of the recent publications relevant to the generation and characterization of hESC- and iPSC-derived erythroid cells and discuss challenges to be met before the eventual realization of clinical usage of these cells.